Roles of ERK/Akt signals in mitochondria-dependent and endoplasmic reticulum stress-triggered neuronal cell apoptosis induced by 4-methyl-2, 4-bis(4-hydroxyphenyl)pent-1-ene, a major active metabolite of bisphenol A. (15th May 2021) - Huang, Chun-Fa; Liu, Shing-Hwa; Su, Chin-Chuan; Fang, Kai-Min; Yen, Cheng-Chieh; Yang, Ching-Yao; Tang, Feng-Cheng; Liu, Jui-Ming; Wu, Chin-Ching; Lee, Kuan-I; Chen, Ya-Wen
Highlights: 4-methyl-2, 4-bis(4-hydroxyphenyl)pent-1-ene (MBP) is a major active metabolite of bisphenol A. MBP induced neuronal cell death underwent apoptotic pathway. MBP regulated mitochondria-dependent and ER stress-triggered neuronal cell apoptosis. The interplay of ERK and Akt signals involved in MBP-induced neurotoxicity. Abstract: Bisphenol A (BPA) is recognized as a harmful pollutant in the worldwide. Growing studies have reported that BPA can cause adverse effects and diseases in human, and link to a potential risk factor for development of neurodegenerative diseases (NDs). 4-methyl-2, 4-bis(4-hydroxyphenyl)pent-1-ene (MBP), which generated in the mammalian liver after BPA exposure, is a major active metabolite of BPA. MBP has been suggested to exert greater toxicity than BPA. However, the molecular mechanism of MBP on the neuronal cytotoxicity remains unclear. In this study, MBP exposure significantly reduced Neuro-2a cell viability and induced apoptotic events that MBP (5–15 μM) exhibited greater neuronal cytotoxicity than BPA (50–100 μM). The mitochondria-dependent apoptotic signals including the decrease in mitochondrial membrane potential (MMP) and the increase in cytosolic apoptosis-induced factor (AIF), cytochrome c release, and Bax protein expression were involved in MBP (10 μM)-induced Neuro-2a cell death. Exposure of Neuro-2a cells to MBP (10 μM) also triggered endoplasmic reticulum (ER) stress through the induction of several key molecules including glucose-regulated protein (GRP)78, C/EBP homologous protein (CHOP), X-box binding protein (XBP)-1, protein kinase R-like ER kinase (PERK), eukaryotic initiation factor 2α (eIF2α), inositol-requiring enzyme(IRE)-1, activation transcription factor(AFT)4 and ATF6, and caspase-12. Pretreatment with 4-PBA (an ER stress inhibitor) and specific siRNAs for GRP78, CHOP, and XBP-1 significantly suppressed the expression of these ER stress-related proteins and the activation of caspase-12/-3/-7 in MBP-exposed Neuro-2a cells. Furthermore, MBP (10 μM) exposure dramatically increased the activation of extracellular regulated protein (ERK)1/2 and decreased Akt phosphorylation. Pretreatment with PD98059 (an ERK1/2 inhibitor) and transfection with the overexpression of activation of Akt1 (myr- Akt1 ) effectively suppressed MBP-induced apoptotic and ER stress-related signals. Collectively, these results demonstrate that MBP exposure exerts neuronal cytotoxicity via the interplay of ERK activation and Akt inactivation-regulated mitochondria-dependent and ER stress-triggered apoptotic pathway, which ultimately leads to neuronal cell death.